Gestión de cuentas por cobrar y su efecto en la liquidez del gobierno autónomo descentralizado municipal del cantón buena fe. periodo 2017 – 2019 - Carriel Garcia, Ruth Maribel (2020)
This research is focused on the evaluation of accounts receivable and their effect on the liquidity of the Municipal GAD of the Canton San Jacinto de Buena Fe during the period 2017 - 2019. For this, interviews with officials and surveys of taxpayers, where inconsistencies in the accounts receivable management process were detected, such as: Duplicate data or erroneous information in the Taxpayers' Database, lack of culture regarding the payment of taxes, there are no alternative methods for notification and form of payment of pending taxes, among others. The delinquency (81.86%) and liquidity (1.81) indices and an Accumulated Overdue Portfolio of $ 2,254,669.69 were determined, with the rustic property tax being the highest. The management of accounts receivable is rated from Fair to Poor and to improve this indicator it is recommended to implement alternative notification methods and forms of payments such as: email, phone call and text messages, payment agreements, debits. Bank account, web payment and home collection for the recovery of the overdue portfolio of the Buena Fe municipality. Keywords: Accounts receivable, Liquidity, Delinquency, Municipality, Government Institution.